Analysis of heritage conservation management using geographic information system - 491184 Aulia Muflin Nasution; Fakulti Alam Bina (2009)
Thesis (Sarjana Sains (Perancangan-Teknologi Maklumat)) - Universiti Teknologi Malaysia, 2009